Willingness to pay for social health insurance among academic staff of a public university in Malaysia - Mohammad Salameh, Ahmad Mustafa; Juni, Muhamad Hanafiah; Kadir @ Shahar, Hayati (Community Health Society Malaysia, 2015)
Introduction: Health care in Malaysia is funded primarily through taxation and is no longer sustainable. One of the funding options is social health insurance (SHI), which provides insurance coverage for those who are unable to benefit immediately from private health insurance plan. This study is performed to assess the willingness of academic staff of a public university in Malaysia to participate in a SHI scheme and level of their willingness to pay (WTP) for SHI. Methodology: A cross-sectional study was performed among staff of a public university between Aprial to June 2015. The stratified random sampling technique was used amongst selected faculties serving as a strata. A self-administered questionnaire consisted of Contingent Valuation (CV) method in evaluating the WTP for the described SHI scheme, was used in this study. The respondents were first asked to select their preferred health financing plan from three plans (out-of-pocket payment, compulsory social health insurance and voluntary health insurance). Next, they were asked if they agreed to join SHI for RM 20. Irrespective of their answer (yes/no), maximum amount they would be willing to pay for the SHI scheme was further assessed. Results: Fifty-eight percent of the participants were females, with majority of respondents age between 41-50 years old, 70.7% (N = 198) of the respondents have 4 to 6 family members with majority of whom had a monthly income of RM5000.00 to RM10000.00. The results indicated that more than 72.5% of the respondents were willing to pay an average of RM79.32 per month per household towards SHI. This level of WTP were significantly associated with age (P=0.002), educational level (P=0.009), seniority (P<0.001), and mean monthly income (P=0.037). However other factors such as ethnicity, religion and family size were not associated with respondents’ level of WTP. Conclusion: Our findings suggest that academic staff of a public university is willing to pay for SHI. The level of WTP was associated with age, education level, seniority and mean of monthly income.